Silence at the end of the rainbow : an analysis of the effects of rainbowism on post-apartheid South African cinema - Slade, Luke (Centre for Film and Media Studies, 2015)
If one reads a broad sample of interviews that have been conducted with South African filmmakers or film writers, then one might start to see a pattern in the types of complaints that emerge. Among these common complaints, one finds a widespread belief that the state is generally unwilling to fund certain types of films, and that contemporary South African audiences will avoid certain types of films. This dissertation explored whether the concept of Rainbowism could be adapted to theorise some reasons as to why the South African film industry seems to privilege certain narratives, whilst silencing others. A situation that is troubling when one considers South Africa's recent history. To accomplish this task, the author did a vast amount of reading on the subject of Rainbowism in general and on post-apartheid South African cinema in particular. From these numerous sources a way forward was synthesised. Rainbowism was defined in terms of myth and counter myth and its role in the creation of a new post-apartheid South African identity was also explored. Following this, South African cinema was historically contextualised and the state film-funding environment was explored. This was done in order to see the engagement between Rainbowism and the various funding bodies. It was shown that the emphasis on adapting to the post-apartheid state's neo-liberal economic policies had resulted in a situation in which film financing bodies such as the National Film and Video Foundation did not allow for audiences to grow in response to films. Rather, films had to be tailored to suit the preferences of existing audiences. This had a negative effect on those filmmakers that sought to try new things for which there might not yet have been an audience. Furthermore, it was also shown that South Africa's relatively peaceful transition from apartheid to democracy has become a feature of international co-productions; the desire to sell the idea of the rainbow nation has effected the types of engagements with the past that are displayed in these films.